2021
DOI: 10.3390/app11188648
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Stress Levels Measured by a Questionnaire and the Data Obtained by Smart Glasses and Finger Pulse Oximeters among Polish Dental Students

Abstract: Stress is a physical, mental, or emotional response to a change and is a significant problem in modern society. In addition to questionnaires, levels of stress may be assessed by monitoring physiological signals, such as via photoplethysmogram (PPG), electroencephalogram (EEG), electrocardiogram (ECG), electrodermal activity (EDA), facial expressions, and head and body movements. In our study, we attempted to find the relationship between the perceived stress level and physiological signals, such as heart rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
1
2
0
Order By: Relevance
“…The smaller of pNN50 and Mrr indicated lower heartbeat variability, so subjects' arousal was increased, meaning that the PSNS activity decreased. These results were consistent with previous studies where HR increased during stressful tasks [73].…”
Section: Stress Recognitionsupporting
confidence: 94%
See 1 more Smart Citation
“…The smaller of pNN50 and Mrr indicated lower heartbeat variability, so subjects' arousal was increased, meaning that the PSNS activity decreased. These results were consistent with previous studies where HR increased during stressful tasks [73].…”
Section: Stress Recognitionsupporting
confidence: 94%
“…Using different sources of bio-signals to detect stress, several studies have shown that features coming from the ECG signal are significant [60], have high correlation indexes with the perceived stress level (PSS) [73], and very high accuracy rates [72].…”
Section: Stress Recognitionmentioning
confidence: 99%
“…These physiological changes have led to the use of various devices to detect public speaking anxiety by recording changes in heart rate ( Croft et al, 2004 ), blood oxygen saturation ( Mocny-Pachońska et al, 2021 ), skin conductance ( Kimani and Bickmore, 2019 ), or cortical activity ( Miskovic et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%